IoT and Sensor Technologies: Revolutionizing Connectivity and Data Insights - Aditya Navrange; Niranjan Shinde (International Journal of Radio Frequency Innovations, 2025)
The Internet of Things (IoT) and sensor technologies have become integral components of modern technological ecosystems, fostering unprecedented levels of connectivity and data acquisition across various sectors. These technologies are pushing the boundaries of what is possible in the way devices interact, collect data, and make decisions autonomously. IoT and sensor technologies have a wide range of applications, spanning healthcare, agriculture, smart cities, and industrial automation, with their potential continually expanding. This paper provides a comprehensive exploration of IoT and sensor technologies, starting with an overview of their definitions and historical context, followed by an analysis of their architecture, types of sensors, and diverse applications across industries. The paper also discusses the challenges and limitations facing IoT and sensor technologies, such as security, privacy, and scalability issues, while exploring future trends and potential advancements in this rapidly evolving field.
Keywords: Data Insights; Internet of things(IoT); Sensor Technologies; connectivity; industrial automation